PERTANGGUNG JAWABAN TINDAK PIDANA PERDAGANGAN ORANG (ANAK) MELALUI PROSTITUSI ONLINE - Riski Akbari; Sukmareni Sukmareni; Riki Zulfiko (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Trafficking in persons is one of the crimes that occur in a country or region by using violence, fraud, and coercion against others with the aim of committing acts of commercialisation of sex and to perform forced labour services. The results of this study can raise awareness in the community of how important the right to freedom is in determining one's life. This study aims to determine the judge's consideration in handing down a verdict on the act of trafficking in persons, the prosecutor's and judge's considerations regarding the defendant's responsibility in case verdict Number: 347/Pid.Sus/2019/PN Pdg. The methodology used in this research is normative jurisprudence, the results of this study indicate that the prosecutor and the judge as in giving a verdict to the defendant and not in accordance with Law Number 21 of 2007 concerning the eradication of criminal acts of trafficking in persons, and how the view of the law in addressing issues regarding trafficking in persons and the form of legal certainty obtained in the event of trafficking in persons.